2006
DOI: 10.12968/jowc.2006.15.5.26909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a sustained silver-releasing dressing on ulcers with delayed healing: the CONTOP study

Abstract: This large-scale comparative real-life study shows that the silver foam dressing supports faster healing of delayed healing wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 10 publications
2
80
0
7
Order By: Relevance
“…No data were available at the time of this review to support the current widespread use of silver-containing dressings, confirming another recent review [81]. Although a single study had compared the use of a silver-containing dressing with usual care in a mixed population of chronic wounds, it was not included in this review because of lack of clear presentation of the subpopulation (8%) with diabetic foot ulcers, even though it was reported that there was no apparent effect on healing in this small group [82]. The group of agents for which there exists some evidence of effectiveness is the hydrogels, as has been noted previously [83,84], but further studies are required.…”
Section: Discussionsupporting
confidence: 66%
“…No data were available at the time of this review to support the current widespread use of silver-containing dressings, confirming another recent review [81]. Although a single study had compared the use of a silver-containing dressing with usual care in a mixed population of chronic wounds, it was not included in this review because of lack of clear presentation of the subpopulation (8%) with diabetic foot ulcers, even though it was reported that there was no apparent effect on healing in this small group [82]. The group of agents for which there exists some evidence of effectiveness is the hydrogels, as has been noted previously [83,84], but further studies are required.…”
Section: Discussionsupporting
confidence: 66%
“…8 Munter reported that silver dressing supports faster healing of delayed healing wounds. 3 No adverse reaction was observed in the study group where as in the control group 23.33 % (7) patients had adverse reactions which included itching and hyperpigmentation (Table 16). …”
Section: Discussionmentioning
confidence: 89%
“…3 Epithelialization was more than 50% at the end of treatment. Caruso DM showed majority of wound treated with silver dressing decreased in size (70%) and increased epithelialization more than 50% with decreased exudates, decreased purulence and resolution of surface slough.…”
Section: Discussionmentioning
confidence: 95%
“…In VLUs without a wound infection (HS 2), moist wound dressings (SoC) are applied [cf.4]. The number of weekly dressing changes is set to 2.5 in both HS 1 and 2 [7,9,18]. …”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that the choice of dressing does not have an impact on ulcer recurrence. The chosen recurrence rate refers to antimicrobial and standard dressings [18]. 2 2

Further assumptions are presented in Appendix 2.

The transition probabilities can be found in Table 1:…”
Section: Methodsmentioning
confidence: 99%